The Poem And The Resistance To White-based Narrative Of History: Analysis Of The Poem: "let History Be Present" By "mourid Al-barghouthi" - saadi, djmouai (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract: Poetry has always been linked to resistance, in this regard, the poem stands as the expression of confrontation, of resilience, and it has become a form of activism and one of the images of the defense of human dignity, of the refusal of repression and hegemony, of exile and marginalization. The poem has to free the imagination and imaginary from stereotypes. This study aims to feature the processes in which this poem functions as an act of resistance and as an interrogation of History to deconstruct its mythology, the misconducts of Western-centrism, and colonial desires. It is also a question of disproving the historical narrative based on the excessive importance given to Western historiography in the face of the cover-up of the historical dynamics of other nations. The poem focuses, as well, on the recall of elapsed History that must be rehabilitated and strengthened. Besides, it is attentive to the opposition of the forms of concealment and methodical marginalization practiced by historiographies and colonial narratives.